Building World Hubs for Talents: Understanding Foreign Student Employment Policy Development in China Through the Multiple Streams Framework - Yalun An; Baocun Liu; Jun Wang (SAGE Open, 2025)
In an evolving global knowledge economy, many countries are actively implementing policies to recruit and retain foreign students as potential global talents and valuable human resources. This article provides a comprehensive review of the evolution of foreign student employment policy in China. The study finds that foreign student employment policy covers three distinct phases: (1) preparation phase (1949–1978) in which few internships, no employment or startups were allowed; (2) construction phase (1979–2009) in which internships and work-study were allowed with complicated procedures; (3) deepening reform phase (2010 to the present) in which qualified foreign students can take part-time jobs, startup business and even immigrate after graduation. The rationales, guidelines and objectives in each policy phase are identified by inductive document analysis using NVivo qualitative software. Moreover, the result of inductive document analysis is converted into the Multiple Streams Framework (MSF) for further analysis. The MSF analysis shows that domestic demands and overseas competition for global talents in the problem stream, together with advocates in policy community inspired by the Party’s ideology of talent development eventually opens a decision window from the political stream. Lastly, this article proposes a modified MSF to better explain agenda setting and policymaking processes in non-Western contexts like China, and calls for more contributions in the MSF-related research.